Combining Acceptance and Commitment Therapy With Adventure Therapy to Promote Psychological Wellbeing for Children At-Risk - Tracey, Danielle; Gray, Tonia; Truong, Son; Ward, Kumara (Frontiers in Psychology, 2018)
With high rates of psychological distress reported amongst children internationally, the development and evaluation of new program initiatives is critical in order to meet the challenge of this burgeoning issue. Both acceptance and commitment therapy and adventure therapy are emerging as popular strategies to elevate psychological wellbeing. This small-scale program evaluation focuses on nine upper primary school-aged children enrolled in a specialist school in Australia for children with challenging behavior and/or emotional needs. Participants completed a newly developed 8-week intervention entitled ‘ACT in the Outdoors’ which combined key principles of both acceptance and commitment therapy and adventure therapy. The program was evaluated via a combination of pre and post participant psychological measures, and post interviews with participants and teachers. The results of this small-scale preliminary evaluation suggest that a portion of the participating children reported improvements in psychological wellbeing and skill development. Improvements appear to be mitigated by attendance and level of psychological wellbeing upon program entry. Based on this premise, the results suggest that more research is warranted to further understand the potential benefit of this innovative interdisciplinary approach.